Comparative Study of Sex Selection in Assisted Reproductive Technology’s Regulation Between Indonesia and England - Rani Tiyas Budiyanti; Anggita Doramia Lumbanraja (SOEPRA, 2020)
Sex selection through assisted reproduction technology can be done by sperm sorting and Pre-Implantation Genetic Diagnosis (PGD) However, there were different regulations in many countries. This study aims to determine the regulation of sex selection with assisted reproductive technology in Indonesia and its comparison with other countries, namely the United Kingdom. This research was a normative study with a comparative and statue approach. Based on research, regulations regarding sex selection with assisted reproduction in Indonesia have been regulated in Government Regulation No. 61 of 2014 concerning Reproductive Health. Indonesia legalizes sex selection by assisting reproduction for second and subsequent children without differentiating the underlying medical and non-medical reasons. The sex selection method regulated in the regulation is the sperm sorting method, whereas, for the PGD method. It has not been regulated further, Indonesia does not yet have further regulations regarding the implementation of sex selection by assisting reproduction along with negative excesses that can occur. Whereas the UK legalizes the selection of sex by assisting reproduction for serious medical reasons and does not allow for non-medical reasons. The sex selection method regulated in the regulation is PGD. Organizing sex selection in the UK will be done after obtaining a license from the Human Fertilization and Embryology Authority (HFEA).